Construction of the Stand and Experimental Studies of the Iontophoresis Process - Michał Gromnicki; Andrzej Bochat (Applied Sciences, 2025)
This paper presents our own design of a research station and exemplary experimental analyses of the iontophoresis process, i.e., a method of electrotransporting substances using direct current. This technique has a wide application in medicine, especially in controlled drug delivery. The first part of this paper discusses the theoretical foundations of iontophoresis, mechanisms of action and its current applications. Then, the design of the research station is described in detail, taking into account its key structural elements, including electrodes made of 316L surgical steel and electrical parameters of work and the adopted research methodology. For the analyzed group of solutions, a power supply with adjustable voltage in the range of 1 to 10 V and current protection up to 400 mA should be used. Additionally, the operation of the constructed setup requires a direct current power source. The tests also showed that the temperature of the solutions, ranging from 26 °C to 40 °C, does not significantly affect the selection of the appropriate power supply for the iontophoresis device. The conducted experimental research clearly demonstrated the usefulness of the setup for identifying the parameters of the iontophoresis process.